Calculation of radiological risks for selected soil samples from the north of Kufa district in Najaf, Iraq - Shaymaa Awad Kadhim; Shahla Alruhaimi; Shatha Alhous; Qassim Shamkhi AL–Khafaji (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate radioactivity levels in soil samples and their physical impact on the population. Methods: The experimental radiation study was conducted in northern Kufa, Al Najaf Governorate, Iraq, in March 2020 by researchers from the Kufa University, Iraq and comprised soil samples. A gamma spectrometer equipped with a sodium iodide detector activated with a trace amount of thallium was used to calculate the concentration of radium, thorium and potassium. Data was analysed using SPSS 20. Results: There were 30 samples. The average concentration of Radium, Thorium and Potassium was (0.824± 0.392)ppm, (1.536± 0.645)ppm and( 0.597± 0.195)%, respectively, and the radiation hazards were lower than the permissible levels. The reported value of excess lifetime cancer risk was (1.2819 ±0.156)×10-3, and the annual gonadal equivalent dose (AGED) was 116.496± 41.255 (mSv. y-1), which was lower than the recommended limit. There was a positive, strong and significant relationship of radium with all the variables (p<0.05) studied except with potassium (p>0.05). Thorium was positively and significantly associated with all the variables (p<0.05). Conclusion: The study area was found to be safe and there was no relationship between the radiation levels of the studied nuclides and the risk of cancer. Key Words: Thorium, Radium, Sodium Iodide, Thallium, Radioactivity, Soil, Potassium Radioisotopes